Evidence based practice at the UKA National Centre for Race Walking - Drake, A. (UKA National Centre for Race Walking, 2009)
Powerpoint from the 1st European Race Walking Conference on evidence based practice at the UKA national centre for race walking: •Strategy & objectives, •Programmecharacteristics, •Race walk athlete development, •Nurturing race walk talent.